Exploring the Effects of Social Stories Intervention on Communication Skills and Anxiety Reduction in Children with Autism - Rodrigues da Silva, Diana; Mwangi, Grace (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to evaluate the effectiveness of a Social Stories intervention in improving communication skills and reducing anxiety in children with autism. A randomized controlled trial was conducted with 30 children diagnosed with Autism Spectrum Disorder in Kenya, aged 6 to 10 years. Participants were randomly assigned to either an intervention group (n = 15) or a control group (n = 15). The intervention group received ten weekly sessions of individualized Social Stories targeting key communication and emotional challenges, each lasting 45–60 minutes, while the control group received no additional intervention beyond routine care. Standardized assessment tools—the Children’s Communication Checklist–2 (CCC-2) and the Spence Children’s Anxiety Scale (SCAS)—were administered at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests in SPSS-27. Results showed significant improvements in communication skills in the intervention group from pre-test (M = 58.34, SD = 6.45) to post-test (M = 66.91, SD = 5.83), maintained at follow-up (M = 65.72, SD = 5.97). Anxiety scores significantly decreased from pre-test (M = 34.87, SD = 4.21) to post-test (M = 26.43, SD = 3.66), with sustained reduction at follow-up (M = 27.14, SD = 3.84). The control group showed no significant changes across time. ANOVA results confirmed significant time × group interactions for both communication (F(2, 84) = 14.86, p < .001) and anxiety (F(2, 84) = 11.53, p < .001), with large effect sizes. Bonferroni tests revealed significant improvements between baseline and both post-test and follow-up points. The findings suggest that Social Stories are an effective and sustainable intervention for enhancing communication skills and reducing anxiety in children with autism, even in low-resource settings.